2012
DOI: 10.1111/j.1751-7176.2012.00690.x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Correlates of Low Medication Adherence in Apparent Treatment‐Resistant Hypertension

Abstract: Low medication adherence may explain part of the high prevalence of apparent treatment resistant hypertension (aTRH). We assessed medication adherence and aTRH among 4,026 participants taking ≥ 3 classes of antihypertensive medication in the population-based REGARDS Study using the 4-item Morisky Medication Adherence Scale (MMAS). Low adherence was defined as a MMAS score ≥ 2. Overall, 66% of participants taking ≥ 3 classes of antihypertensive medication had aTRH. Perfect adherence on the MMAS was reported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 40 publications
5
54
1
3
Order By: Relevance
“…Considering the types of the most prescribed medications in this study, we observe that the rate of adherence found is in agreement with the literature, in which adherence to diabetes and high blood pressure medication ranges from 36% to 66% (22)(23) .…”
Section: As This Study Shows An Association Betweensupporting
confidence: 79%
“…Considering the types of the most prescribed medications in this study, we observe that the rate of adherence found is in agreement with the literature, in which adherence to diabetes and high blood pressure medication ranges from 36% to 66% (22)(23) .…”
Section: As This Study Shows An Association Betweensupporting
confidence: 79%
“…A recent large population-based study in the United States, the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study, also reported very low prevalence of non-adherence of only 8%, using the four-item MMAS. 23 We also identified a higher proportion of females in the non-adherent group, which was consistent with findings from the REGARDS study 23 and one previous study in BMI, body mass index; BP, blood pressure; bpm, beats per minute; CKD, chronic kidney disease; DBP, diastolic blood pressure; ED, erectile dysfunction; eGFR, estimated glomular filtration rate; OSA, obstructive sleep apnea; SBP, systolic blood pressure; TDM, therapeutic drug monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous large studies using patient self-report or medication fill data have demonstrated that adherence is not appreciably different (and perhaps even greater) among patients with RH versus non-RH. 39,40 Finally, this is a retrospective analysis of three cohorts of women with varying underlying CVD and must be taken with a degree of caution. Although our results in women are consistent with studies in other populations, we cannot exclude the possibility that unmeasured confounders impacted our results.…”
Section: Study Limitationsmentioning
confidence: 99%